The Spiritual Pathology of the Heart in the Stories of Pharaoh, Qarun, and Haman: A Thematic Analysis from the Perspective of Tafsir al-Mishbah - Nurmaya Fitri; Muhammad Yasir; Abd. Ghofur (Al-Qudwah: Jurnal Studi Al-Qur'an dan Hadis, 2026)
This study seeks to analyse the manifestations of spiritual pathology of the heart as depicted in the Qur’anic narratives of Pharaoh, Qarun, and Haman, through an integrative approach combining Qur’anic exegesis and psychological perspectives. The significance of this research lies in recognising that the spiritual pathology of the heart are not solely spiritual or theological concerns but are intricately linked to psychological states and the social conduct of modern individuals. Prior investigations into the spiritual pathology of the heart have predominantly adopted normative-theological frameworks or have examined specific figures in a fragmented manner. Consequently, there exists a paucity of comprehensive studies that synthesise Qur’anic interpretation with psychological methodologies. Employing a qualitative methodology grounded in library research and utilising the thematic interpretation (maudhu‘ī) approach, this study reveals that Pharaoh, Qarun, and Haman exhibit symptoms indicative of spiritual maladies such as riya’ (showing off), ujub (self-admiration), arrogance, stinginess, ظلم (oppression), and rejection of truth. These spiritual afflictions may precipitate psychological imbalance, thereby influencing moral, spiritual, and social dimensions of life. From a psychological standpoint, the traits and behaviours of these figures bear resemblance to various personality disorders, including narcissistic, antisocial, histrionic, and obsessive-compulsive disorders. This research contributes to an expanded understanding that the spiritual pathology of the heart impact not only spiritual well-being but also moral integrity, mental health, and social equilibrium. Accordingly, these Qur’anic narratives may function as ethical exemplars to deter the emergence of destructive behaviours in contemporary society.